A magnetic Bi-stable nonlinear energy sink for structural seismic control. (12th May 2020) - Chen, Yang-Yang; Qian, Zhi-Chao; Zhao, Wei; Chang, Chia-Ming
Abstract: In this paper, a magnetic bi-stable NES (MNES) is proposed for structural seismic control. Permanent magnets are configured to generate noncontact and smooth bi-stable restoring force for the present MNES device, by which the transient internal resonance between the primary structure and the attached MNES can be rapidly enhanced under seismic excitation. The governing equation of the present MNES is derived, and the numerical parameter optimization is carried out for its implementation in seismic control for a shear frame model. Seismic performance of this frame structure attached with the proposed MNES is evaluated, and compared to those of cubic NES and linear tuned mass damper (TMD) systems. As shown in the results, the proposed MNES is found to be robustly capable of protecting the shear frame under seismic excitations. Immediate cascade of broadband transient internal resonance captures under seismic excitations are found as the essential cause of the high efficiency of the present MNES system.